IMPLEMENTASI KOMPETENSI INTI SATU DAN DUA KURIKULUM 2013 DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VIII SMPN 1 KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH TAHUN PELAJARAN 2016/2017 - Riyansa Riyansa; Ria Ariesta; Padi Utomo (Jurnal Korpus, 2017)
The purpose of this study is to describe the implementation of the core competencies one and two Curriculum 2013 in learning Indonesian students class VIII SMPN 1 Kecamatan Pondok Kelapa Central Bengkulu District Lessons 2016/2017. The method used in this research is descriptive qualitative method. The subject of this research is one Indonesian teacher who teaches in class VIII SMPN 1 Kecamatan Pondok Kelapa, Central Bengkulu Regency. Technique of collecting data using observation and interview. Data analysis techniques used are Miles and Huberman which includes data collection, data reduction, data presentation, and data verification. Test the validity of the data using credibility test conducted by triangulation. The results showed that the teacher has implemented the core competence of one / spiritual attitude through the activity of saying and responding greetings, praying together, performing the prayers at school and keeping the environment around the school. While the two core competencies / social attitudes are integrated through group learning activities, not cheating or plagiarism, speaking honestly, working on and collecting tasks on time, obeying school rules, performing individual duties well, daring to perform in class, be responsible and accept The risks of action, respect for the elderly, not forcing opinions, helping each other to achieve mutual success, taking an active role, asking, answering, not despairing, daring to accept others politely and politely fellow.